2021
DOI: 10.1002/dvdy.324
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage‐ and expression‐based inference of the roles of forkhead box transcription factor Foxc2 in craniofacial development

Abstract: Background Foxc2 is a member of the winged helix/forkhead (Fox) box family of transcription factors. Loss of function of Foxc2 causes craniofacial abnormalities such as cleft palate and deformed cranial base, but its role during craniofacial development remains to be elucidated. Results The contributions of Foxc2‐positive and its descendant cells to the craniofacial structure at E18.5 were examined using a tamoxifen‐inducible Cre driver mouse (Foxc2‐CreERT2) crossed with the R26R‐LacZ reporter mouse. Foxc2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Foxc2 is a member of the fork head box family of transcription factors and has been shown to be functional during the development of cranial mesenchymal tissues [37]. The loss of function in Foxc2 results in craniofacial anomalies, notably CP, but the mechanism is unclear [38]. In the present study, a decline in Foxc2 expression was observed as the embryo matured, with potential influences from increased miR-744-5p in ASVs.…”
Section: Discussionmentioning
confidence: 49%
“…Foxc2 is a member of the fork head box family of transcription factors and has been shown to be functional during the development of cranial mesenchymal tissues [37]. The loss of function in Foxc2 results in craniofacial anomalies, notably CP, but the mechanism is unclear [38]. In the present study, a decline in Foxc2 expression was observed as the embryo matured, with potential influences from increased miR-744-5p in ASVs.…”
Section: Discussionmentioning
confidence: 49%
“…Foxc2 could cooperate with Foxc1 in the development of the cranial base, since both are co-expressed in this area during mouse craniofacial development. Foxc2 silencing through the Cre-recombinant system showed a lack of ossification in the presphenoid, while Foxc1 silencing exhibit a non-ossification of the presphenoid, a deformed alisphenoid, and severe loss in the anterior part of the basisphenoid ( Takenoshita et al, 2021 ). These studies introduce Fox proteins as important players to consider during craniofacial development.…”
Section: Fox Transcription Factors As a Potential Connection Between Serotonin Deregulation And Disrupted Cranial Stem Cell Biologymentioning
confidence: 99%
“…In this review, we propose that the transcription factor FoxO1 could be implicated linking the misregulation of serotonin levels with the different processes affected during craniofacial formation, disrupting the stem/progenitor cell biology. FoxO1 has a role in craniofacial tissue development (bone, cartilage, and tooth) and function within the stem cell regulation ( Xu et al, 2018 , 2021 ; Takenoshita et al, 2021 ). Moreover, it has a capacity to respond to changes in serotonin concentrations, being involved in the manifestation of major depressive disorders ( Polter et al, 2009 ; Wang et al, 2015 ).…”
Section: Future Perspectivesmentioning
confidence: 99%